MEGA-AUTHORSHIP FROM A BIBLIOMETRIC POINT OF VIEW - Sen, B.K. (Malaysian Journal of Library and Information Science, 1997)
A research contribution by ten or more authors has been termed as the work of mega-authorship. The study conducted with a sample of 1294 papers published in the Proceedings of the National Academy of Sciences of the United States of America during February - July 1996 shows that about 5% of the papers fall under the category of mega-authorship. Mega-authorship seems to picture better the international collaborative scenario in the field of scientific research. Attempts to identify the causes of mega-authorship and discuss its impact on author indexes, indexing services, citations, and the problem it may create in the identification of the principal contributor of a basic idea.